2019
DOI: 10.1093/eurheartj/ehz591
|View full text |Cite
|
Sign up to set email alerts
|

Clonal haematopoiesis in patients with degenerative aortic valve stenosis undergoing transcatheter aortic valve implantation

Abstract: Aims Clonal haematopoiesis of indeterminate potential (CHIP), defined as the presence of an expanded somatic blood cell clone without other haematological abnormalities, was recently shown to increase with age and is associated with coronary artery disease and calcification. The most commonly mutated CHIP genes, DNMT3A and TET2, were shown to regulate inflammatory potential of circulating leucocytes. The incidence of degenerative calcified aortic valve (AV) stenosis increases with age and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 172 publications
(149 citation statements)
references
References 17 publications
5
140
1
3
Order By: Relevance
“…The VAF of clonal populations was associated with the severity of the clinical outcome, suggesting a dose-response relationship [58]. Similarly, aortic valve stenosis patients with DNMT3A or TET2 variants who underwent aortic valve implantation surgery were observed to have heightened medium-term all-cause mortality compared to those without CHIP mutations [59]. These results were supported by the finding that mice with hematopoietic or myeloid Tet2-deficiency had greater cardiac dysfunction and worsened remodeling following induced heart failure [60].…”
Section: Chip and Comorbid Diseasesmentioning
confidence: 84%
“…The VAF of clonal populations was associated with the severity of the clinical outcome, suggesting a dose-response relationship [58]. Similarly, aortic valve stenosis patients with DNMT3A or TET2 variants who underwent aortic valve implantation surgery were observed to have heightened medium-term all-cause mortality compared to those without CHIP mutations [59]. These results were supported by the finding that mice with hematopoietic or myeloid Tet2-deficiency had greater cardiac dysfunction and worsened remodeling following induced heart failure [60].…”
Section: Chip and Comorbid Diseasesmentioning
confidence: 84%
“…CHIP-related mutations can also impair the function of T cells. Clinical data reported by Zeiher et al showed that, among a population of patients with degenerative aortic stenosis undergoing transcatheter aortic valve implantation (TAVI), those carrying a DNMT3A mutation had an increased Th17/Treg ratio [15]. This was not observed in patients harboring a TET2 mutation.…”
Section: The Interplay Of Chip Immune Dysregulation and Cardiovascumentioning
confidence: 98%
“…In this view, recently uncovered genetic factors and acquired risk factors collaborate to induce a heightened chronic pro-inflammatory tone and multi-organ subclinical dysfunction, respectively, thus defining a HFpEF predisposition. In the premalignant syndrome of clonal hematopoiesis of indeterminate potential (CHIP), inactivating mutations in genes controlling hematopoietic stem cell turnover and differentiation leads to enhanced proliferation of myeloid cells with pro-inflammatory properties, and to an increased T helper 17 (Th17) / regulatory T cell (Treg) ratio [15] (first hit). Furthermore, pro-inflammatory circulating immune cells are recruited into the heart by danger signals produced in the myocardium in response to traditional risk factors such as elevated BP, aortic valve stenosis, smoking and/or aging (second hit), with endothelial activation facilitating the immune cell influx [9,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In retrospective cohort studies of >10,000 participants, CHIP associated with atherosclerotic cardiovascular disease and related complications (myocardial infarction and stroke, albeit with lower burdens of risk than hematologic malignancy) [9,10,21]. Moreover, smaller retrospective studies reveal CHIP as a disease modifier in heart failure and valvulopathy [22,23], further suggesting a role for TET2 and DNMT3A mutant monocytes in disease exacerbation. Whereas a causative association between CHIP and atherosclerotic disease and heart failure in humans is further supported by studies in vitro and in mice, other disease correlations with CHIP lack robust causative and mechanistic evidence.…”
mentioning
confidence: 99%